Low Solar Coronal Thermal Structure Derived from Magnetohydrostatic Model - Setiahadi, Bambang (Prosiding SNPBS (Seminar Nasional Pendidikan Biologi dan Saintek), 2017)
By assuming the Sun in quiet condition we derived coronal thermal structure for low solar coronal magneto- plasma atmosphere. Ideal gas law in a static equilibrium configuration in coronal magnetic plasma state isderived and the solution may be directed to figure-out the thermal structure in mixed plasma and magneticfields within the low corona. The results show that corona may have hot and ‘cool’ solution in low coronaunder the condition when the Sun in quiet condition.